Clinical and pharmacological characteristics of antianginal and anti-ischemic drugs - Резніченко, Олександр; Reznichenko, Oleksandr; Шерстюк, Людмила; Sherstiuk, Liudmyla; Власенко, Ольга; Vlasenko, Olga; Гріднєва, Світлана; Grydnieva, Svitlana; Вовк, Кіра; Vovk, Kira; Бєляєва, Людмила; Belyaeva, Ludmila (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Since the emergence of the principles of evidence-based medicine, drug therapy has become one of the most dynamically developing branches of medicine. Currently, according to the Ministry of Health, over 12 thousand medicines are registered on the Ukrainian pharmaceutical market, which gives the doctor the opportunity to choose the most effective drug strategy in terms of an individualized approach to patients. The large number of drugs makes it difficult to make the best choice when choosing a drug to provide both clinically and cost-effective and safe treatments. Despite the existing strict recommendations for the treatment of certain diseases, it is necessary to move away from templates, and when choosing drugs, to use an individualized approach to each patient, which in turn requires deep knowledge, the use of scientifically based methods of pharmacotherapy. It is these tasks that are provided by clinical pharmacology, which in its essence is a methodology for the choice of drug therapy.
Methodical instructions for practical classes of students of higher medical education in the 5th year of study  the discipline of "Clinical Pharmacology"
Keywords: MEDICINE::Physiology and pharmacology; MEDICINE::Physiology and pharmacology::Pharmacological research::Clinical pharmacology; antianginal; anti-ischemic; drug treatment; Физиологія та фармакологія; Клінічна фармакологія; антиангінальний; протиішемічний; медикаментозна терапія